2015
DOI: 10.11622/smedj.2015166
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence for endolymphatic sac surgery in the treatment of Meniere’s disease: a systematic review

Abstract: This paper aims to identify emerging evidence for endolymphatic sac surgery (ESS) in the treatment of Meniere's disease since the landmark study by Thomsen et al, published in 1998Thomsen et al, published in (conducted from 1981Thomsen et al, published in to 1989. Using the MEDLINE database (PubMed), a systematic review of the literature published from January 1990 to June 2014 was performed. We included all English-language, peer-reviewed randomised controlled trials (RCTs) and controlled studies. Single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…As such, based on the current evidence, it is not possible to conclude whether endolymphatic surgery in Menière's disease yields any positive results aside from a potential placebo effect. This is in line with the conclusions of other systematic reviews previously published on this matter [12,15].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As such, based on the current evidence, it is not possible to conclude whether endolymphatic surgery in Menière's disease yields any positive results aside from a potential placebo effect. This is in line with the conclusions of other systematic reviews previously published on this matter [12,15].…”
Section: Discussionsupporting
confidence: 93%
“…In the search for systematic reviews, we identified references. Following removal of duplicates and none-relevant references, we identified seven systematic reviews [10][11][12][13][14][15][16] that we obtained in full text and read thoroughly. Of these, one systematic Cochrane review [15], which included three relevant RCTs, matched our clinical question,.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While these techniques are considered nondestructive procedures as they preserve the auditory function, transmastoid labyrinthectomy is completely destructive to the labyrinth and is indicated only in patients with established nonserviceable hearing loss and persistent recurrent vertigo attacks. [106][107][108][109][110][111][112] -Vestibular rehabilitation: It could be proposed in patients with MD with an established vestibular deficit to facilitate vestibular compensation. However, in the initial years of the disease, its usefulness is controversial.…”
Section: Treatmentmentioning
confidence: 99%
“…A famous study conducted by Thomsen et al [7,8] in 1981 and concluded in 1986 compared sac shunting to a placebo procedure (mastoidectomy) and found no benefit of the endolymphatic sac (ELS) shunting procedure; their analysis was later criticized by Welling and Nagaraja [9] . Sac shunting was found to be effective in this instance, but data remains variable and controversial in several studies [10] . A meta-analysis in 2014 by Sood et al [11] found that sac decompression and sac shunting both achieve approximately 75% vertigo control with hearing preservation in favor of decompression.…”
Section: Introductionmentioning
confidence: 90%